Multivariable System with Level Control. (2016) - Dulău, Mircea; Dulău, Tudor-Mircea
Abstract: The paper presents the mathematical modeling procedure of a multivariable process with two coupled tanks and it is determined the multivariable control algorithms, imposing a desired behavior of the closed-loop and open-loop system. They ensure the imposed performances on direct connection channels, compensate the effect of the inter-influences between channels, and the system operates decoupled. The control algorithms resulted by the design are high-order, so, based on the Hankel norm, there are determined the truncated (reduced) forms of the controllers. The computing, as well as the behavior of the system, are performed using the Matlab environment.